Icu.now : an awareness campaign for foreign domestic workers. - Lim, Yi Xiu. (2012)
icu.now recognises the contributions and sacrifices made by a group of ‘invisible individuals’ residing in Singapore (1 in every 5 households): foreign domestic workers, known colloquially as maids. icu.now aims to highlight the plight of domestic workers, provide deeper insights into the challenging demands of domestic jobs, and most crucially, to promote better treatment of domestic workers; such as championing a mandatory day-off for all. icu.now wants current and future employers to start seeing their domestic workers as equals. icu.now explores the impact of the design community in enabling contributions, participation and communication in society through the power of graphic design.